POSSIBILITIES OF ULTRASOUND METHOD OF RESEARCH IN EARLY DIAGNOSTICS OF THYROID CARCINOMA - A. M. Shulutko; V. I. Semikov; A. P. Patalova; A. V. Gorbacheva; S. E. Gryaznov; G. T. Mansurova; Yu. A. Boblak (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. This study evaluated the possibilities of ultrasound in diagnostics of early thyroid carcinoma. MATERIALS AND METHODS. The authors have compared the ultrasound results with data of postoperative histological examination in 106 patients with differentiated thyroid carcinoma. There were 140 patients with nodular proliferating colloid goiter and 42 patients with follicular thyroid adenomas. RESULTS. The individual ultrasound signs of differentiated thyroid tumors with the size of 1cm in diameter were determined. The ultrasound symptom complex of papilliary carcinoma was defined. Ultrasound features of follicular carcinoma were nonspecific. Noncapsulation papillary carcinoma had pathognomonic ultrasound picture. The ultrasound image of follicular and papillary carcinoma would be similar in presence of capsule. CONCLUSIONS. The accurate analysis of ultrasound image gave the possibility of diagnostics of papilliary carcinoma at early stage with high degree of probability.